Nutritive values of hay from siratro (Phaseolus atropurpureus) cut at different stages of development - Lima, Carlos Rodrigues; Souto, Sebastião Manhães; Garcia, José Maurício Reis; Araújo, Maria Ribeiro (Pesquisa Agropecuaria Brasileira, 2014)
A digestion trial was conducted with sheep to determine the nutritive value of Siratro (Phaseolus atropurpureus) hay, at different vegetation stages. The total collection technique was used. The following variations in the crude fractions were observed: dry matter: 81.42-90.36%; protein: 13.82-17,97%; ether extract: 1.88-3.01%; fiber: 33.16-40,69%; minerals: 7,14-15.78% and nitrogen free extract: 22.53-39.5% .Average crude protein content was higher than for other tropical legumes. The observed digestibility coefficients were as follows: dry matter, 41.95-70,55%; protein, 67.18-81.1%; ether extract, 31.90-75.28%; fiber, 31.23-65.94% and nitrogen free extract, 48.61-78.45%. Digestibility coefficients for crude protein and crude fiber and digestible protein on dry matter basis were higher in hays from plants at more advanced stage of vegetative growth. Significant differences (p